Digitization of Inland Water Resources for Fisheries through Remote Sensing and Geographical Information System - A Study in Ratnagiri District - Lokhande, P. C.; Shirdhankar, M. M.; Chaudhari, K. J.; Sawant, M. S. (Fishery Technology, 2017)
Natural inland aquatic resources such as rivers, creeks, mangroves as well as manmade resources such as reservoirs, shrimp farms and shrimp hatcheries of Ratnagiri district were mapped using Remote Sensing and Geographical Information System (GIS). IRS P6 LISS III images were used for mapping. A total of 10 rivers, 24 creeks and 2435.16 ha of mangrove area were identified and mapped. There are 65 reservoirs, 40 shrimp farms and 2 hatcheries in the district. Digital maps of each resource with details were incorporated using GIS techniques. IRS P6 LISS III images with 23 m resolution can be processed after enhancing resolution to 15 m by merging with Landset ETM+ image to map inland fisheries resources through Geographical Information System.